PENGARUH RASIO PROFITABILITAS, LIKUIDITAS, DAN FIRM SIZE TERHADAP FINANCIAL DISTRESS (Perusahaan Property & Real Estate yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2020-2022) - Muthi'ah Rahmadian; Suprastha, I Nyoman; Nisa, Chaerani (JIMP : Jurnal Ilmiah Manajemen Pancasila, 2025)
The COVID-19 pandemic that occurred in the world before 2020 has changed the business world drastically, affecting companies in various sectors including property & real estate companies listed on the Indonesia Stock Exchange (IDX). This research aims to determine the influence of profitability, liquidity and firm size ratios on financial distress in properties & real estate companies listed on the IDX for the 2020-2022 period. The research results showed that all of the 8 companies studied experienced financial distress and simultaneously the profitability ratio (ROE), liquidity (CR) and firm size (FS) variables had a significant effect on financial distress (FD). Partially, the profitability and liquidity ratio variables have a significant effect on financial distress, but the firm size variable does not have a significant effect on financial distress. It can be said that the higher the value of the profitability ratio (ROE) variable, the lower the occurrence of financial distress. Then, the lower the value of the liquidity ratio (CR) variable, the lower the occurrence of financial distress. Finally, the firm size variable which does not have a significant effect on financial distress shows that a lower value will also reduce the risk of financial distress, although not significantly.